Cervical Auscultation in Adults Without Complaint of the Deglutition - Cardoso, Maria Cristina de Almeida Freitas; Gomes, Débora Hahn (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Cervical auscultation is a noninvasive test in the noisy swallowing pharyngeal stage.Objective: To verify the sounds of swallowing, the time of its occurrence based on subjective examination of cervical auscultation.Method: Cross-sectional study, clinical and experimental agreement in which participated thirty and two female adults young, mature swallowing pattern. The examination included the orofacial analysis of the orofacial, associated with cervical auscultation of both sides and compared the participants' age. The data were conducted by two examiners and results were compared.Results: There is intermediate or high concordance for most of the measures collected and connected between the evaluators. There was a difference between the sides researched and significant association between the noises of the right and left. Regarding the time of swallowing was observed statistically significant correlation (r = 0.42, p = 0.017) between the mean swallowing, age and time for swallowing solid consistency.Conclusion: Normal swallowing noises vary in relation to the sides of the larynx, the frequency and intensity, but also between the time of occurrence of the transport of the bolus in all consistencies, especially in solids and this time are related to age.
Keywords: auscultation; deglutition; deglutition disorders